Transparency of peer review: a semi-structured interview study with chief editors from social sciences and humanities - Veli-Matti Karhulahti (BMC, 2021)
Abstract Background Open peer review practices are increasing in medicine and life sciences, but in social sciences and humanities (SSH) they are still rare. We aimed to map out how editors of respected SSH journals perceive open peer review, how they balance policy, ethics, and pragmatism in the review processes they oversee, and how they view their own power in the process. Methods We conducted 12 pre-registered semi-structured interviews with editors of respected SSH journals. Interviews consisted of 21 questions and lasted an average of 67 min. Interviews were transcribed, descriptively coded, and organized into code families. Results SSH editors saw anonymized peer review benefits to outweigh those of open peer review. They considered anonymized peer review the “gold standard” that authors and editors are expected to follow to respect institutional policies; moreover, anonymized review was also perceived as ethically superior due to the protection it provides, and more pragmatic due to eased seeking of reviewers. Finally, editors acknowledged their power in the publication process and reported strategies for keeping their work as unbiased as possible. Conclusions Editors of SSH journals preferred the benefits of anonymized peer review over open peer and acknowledged the power they hold in the publication process during which authors are almost completely disclosed to editorial bodies. We recommend journals to communicate the transparency elements of their manuscript review processes by listing all bodies who contributed to the decision on every review stage.